Oxidized cellulose 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) for Mn(II) adsorption - Mahendra, I Putu; Finaritan, Venti; Ramadiani, Dwi Liza; Harianja, Hiskia; Pasaribu, Khatarina Meldawati (Pascasarjana Universitas Negeri Medan, 2024)
The presence of excess Mn²⁺ in water can result in unpleasant odors and tastes, and its consumption can lead to neurological disorders in humans. Adsorption using oxidized cellulose is an efficient method for removing Mn²⁺ ions. In this study, cellulose was oxidized using the TEMPO/NaOCl/NaBr system with varying NaOCl concentrations (5, 15, and 30 mmol/g) to identify the optimum conditions for Mn²⁺ adsorption. The carboxyl group content in the oxidized cellulose samples was 0.2393, 0.2435, and 0.2664 mmol/g, respectively. The adsorption efficiencies were 92.40%, 91.71%, and 91.43%, with the highest efficiency observed at 5 mmol/g NaOCl. The decrease in adsorption efficiency at higher NaOCl concentrations was attributed to the oxidation of secondary hydroxyl groups, forming undesirable ketone groups and disrupting the reaction pathway. FTIR analysis confirmed successful oxidation with a new absorption band at 1646 cm⁻¹. XRD analysis showed an increase in the crystalline index to 82.8%, 83.1%, and 83.13% for NaOCl concentrations of 5, 15, and 30 mmol/g, respectively. This study highlights the potential of TEMPO/NaOCl/NaBr-oxidized cellulose as an effective adsorbent for Mn²⁺ removal under optimized conditions.